Controlled synthesis of luminescent Gd2O3:Eu3+ nanoparticles by alkali ion doping1. Issue 9 (7th March 2015) - Wawrzynczyk, Dominika; Samoć, Marek; Nyk, Marcin
<x xml:space="preserve">Abstract</x> The influence of mono-positive alkali ions (Li+, Na+ and K+) on the growth processes, crystal structure and spectroscopic properties of Gd2O3 colloidal nanoparticles doped with Eu3+ ions was investigated.